TO THE POSSIBILITY OF REVEALING OF SIDE EFFECTS OF METRONIDAZOLE (0,5% INFUSION SOLUTION, 100 ML) IN EXPERIMENT - A. G. Yushkov; N. A. Shulgina; A. A. Gushchina; G. G. Yushkov; M. M. Rasulov; V. V. Benemanskiy; M. M. Boon (Acta Biomedica Scientifica)
An. experimental research, of infusion solution of Metronidazole at single and repeated administration to the animals (rabbits) was carried out. Distinct signs of toxicity of the researched pattern. in the dose that is ten times higher than maximum, daily dose were determined. It concerns statistically reliably changed hematologic, biochemical and. electrophysiological indices that are typical for Metronidazole in particular. Only the fact of increase of content of creatinine in blood serum in 2 weeks after the administration, of the preparation should be registered but in this case it can be the signal to stop further administration, of the preparation.